Am I Needed Here? How Psychological Ownership Explains the relationship between Supervisors’ Support and Workplace Ostracism - Linus Jonathan Vem; Fabian Sylvester Sike; Nelson Chuwang Pam; Abel Daniel Ochigbo; Keng-Kok Tee (SAGE Open)
As the workplace continue to attract all the segments of the diverse society, one stark reality organizations grapple with in recent times is the readiness to inculcate inclusive behaviour among all categories of employees. This study evaluates the role of perceived supervisors’ support (PSS) on perceived workplace ostracism (PWO) through psychological ownership (PO) among federal civil servants working in Plateau state. We draw from affective event theory (AET) and organizational support theory (OST)to justify the hypothesized relationship. Five hundred and twenty-six copies of questionnaires were administered while 332 out of the retrieved were usable. Structural equation modeling through SMART-PLS version 4. was used to analyze the data collected. The results suggest that PSS significantly associate with PWO and psychological ownership mediates the relationship between PSS and PWO. From the results, the study offers a modest theoretical contribution through the connection between AET and OST in justifying the role of PSS and PO in the tested model. Some practical implications for managerial practice were also proffered.